Sweden now 1978-I - Testologen Ltd. (IMU-Testologen AB, 1983)
In the middle of the sixties Testologen AB, in cooperation with a group of advertisers, introduced a new way of investigation where data about the target groups, i.e. interests, consumer habits, possessions, buying intentions, and data about reading habits were collected in the same survey. At SSD there are now surveys available from the Sweden Now series covering the period 1972-1991.
In the 1977 survey the respondents had to indicate their reading habits concerning fifteen different daily papers, weekdays and weekends respectively. They also had to state their reading habits concerning nearly fifty papers from the weekly and monthly press. Other questions dealt with the household´s possession of a number of capital goods such as, car, camera, projector, washing machine, dishwasher, etc. and also if there were any dogs, cats, aquarium fishes or cagebirds in the household. A group of questions is dealing with buying habits and purchasing intentions for a number of products. A number of questions about personal interests are introduced by ´Human interests are different. How great is your interest for the following subjects and activities´. Subsequently the respondent is asked how interested he/she is in buying food, cooking, having guests, leisure time activities, etc. There is information about the respondent´s gender, marital status, age, income, occupation, education and housing, and also about the household´s size, age structure, and total income of household. Sweden Now 1978 is almost a total replication from the year before. A novelty for this survey is that the respondents had to indicate if they agreed or disagreed with a number of statements concerning life style. The number of questions concerning how frequently different shops are visited have been enlarged, while the questions about decisional power in the household have been removed.

Purpose:

Collect broad information about interests, purchasing habits and media choices

In the middle of the sixties Testologen AB, in cooperation with a group of advertisers, introduced a new way of investigation where data about the target groups, i.e. interests, consumer habits, possessions, buying intentions, and data about reading habits were collected in the same survey. At SSD there are now surveys available from the Sweden Now series covering the period 1972-1991.
In the 1977 survey the respondents had to indicate their reading habits concerning fifteen different daily papers, weekdays and weekends respectively. They also had to state their reading habits concerning nearly fifty papers from the weekly and monthly press. Other questions dealt with the household´s possession of a number of capital goods such as, car, camera, projector, washing machine, dishwasher, etc. and also if there were any dogs, cats, aquarium fishes or cagebirds in the household. A group of questions is dealing with buying habits and purchasing intentions for a number of products. A number of questions about personal interests are introduced by ´Human interests are different. How great is your interest for the following subjects and activities´. Subsequently the respondent is asked how interested he/she is in buying food, cooking, having guests, leisure time activities, etc. There is information about the respondent´s gender, marital status, age, income, occupation, education and housing, and also about the household´s size, age structure, and total income of household. Sweden Now 1978 is almost a total replication from the year before. A novelty for this survey is that the respondents had to indicate if they agreed or disagreed with a number of statements concerning life style. The number of questions concerning how frequently different shops are visited have been enlarged, while the questions about decisional power in the household have been removed.

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval
ORVESTO 1978-I
Sverige nu 1978-I
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; shopping; shopping; retail outlets; försäljningsställen; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; membership; medlemskap; attitudes; attityder; drinking behaviour; alkoholvanor; organizations; organisationer; interest (cognitive processes); intresse (kognitiva processer); frequency; frekvens; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap